2017
DOI: 10.1016/j.ejcb.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Huntingtin stimulates capture of retrograde dense-core vesicles to increase synaptic neuropeptide stores

Abstract: The Huntington’s disease protein Huntingtin (Htt) regulates axonal transport of dense-core vesicles (DCVs) containing neurotrophins and neuropeptides. DCVs travel down axons to reach nerve terminals where they are either captured in synaptic boutons to support later release or reverse direction to reenter the axon as part of vesicle circulation. Currently, the impact of Htt on DCV dynamics in the terminal is unknown. Here we report that knockout of Drosophila Htt selectively reduces retrograde DCV flux at prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Since Drosophila NMJs undergo rapid structural and functional changes during larval growth [83], type-1 synaptic boutons between muscles 6/7 at larval abdominal segments A4-A5 of third instar larval were examined. Similar to previous studies [10], htt reduction did not dramatically alter the coordinated growth of NMJs (Fig. S2a).…”
Section: Reduction Of Htt Disrupts the Axonal Motility Of Rab4 Causinsupporting
confidence: 91%
“…Since Drosophila NMJs undergo rapid structural and functional changes during larval growth [83], type-1 synaptic boutons between muscles 6/7 at larval abdominal segments A4-A5 of third instar larval were examined. Similar to previous studies [10], htt reduction did not dramatically alter the coordinated growth of NMJs (Fig. S2a).…”
Section: Reduction Of Htt Disrupts the Axonal Motility Of Rab4 Causinsupporting
confidence: 91%
“…This process has been termed capture and has been measured as the decrease in DCV flux entering and leaving a bouton (Shakiryanova et al, 2006;Wong et al, 2012;Bulgari et al, 2014Bulgari et al, , 2017Cavolo et al, 2016). Notably, this parameter encompasses capture initiation, which when measured over minutes does not quantify the much longer duration of capture (Shakiryanova et al, 2006).…”
Section: Transport and Capture In Type II Arborsmentioning
confidence: 99%
“…Furthermore, synaptic capture of DCVs increases following activity and is constitutively elevated by a transcription factor in specialized neuroendocrine neurons (Shakiryanova et al, 2006;Bulgari et al, 2014;Cavolo et al, 2016). Disease-related proteins such as the fragile-X syndrome protein and huntingtin also influence synaptic neuropeptide stores by regulating direction-specific DCV capture (Cavolo et al, 2016;Bulgari et al, 2017). Thus, synaptic capture is a major determinant of presynaptic accumulation of DCVs and hence affects the capacity for release of DCV contents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation is that kinesin motors more easily release DCVs than dynein motors. The process of DCV release by motors may be differentially controlled (Shakiryanova et al [19], Bulgari et al [3], Cavolo et al [16]).…”
Section: Estimating a Value Of H Axmentioning
confidence: 99%
“…Malfunctions in DCV transport can lead to devastating neurodegenerative diseases. Bulgari et al [3] reported that the loss of Huntingtin protein results in more capture of retrogradely transported DCVs and thus more DCV accumulation in the nerve terminal. They also suggested a possible link between DCV transport and Huntington's disease, caused by accumulation of mutant Huntingtin protein and loss of wild type Huntingtin, through modification of synaptic capture of DCVs.…”
Section: Introductionmentioning
confidence: 99%